Interlaboratory Comparison of Methods To Quantify Microsclerotia of Verticillium dahliae in Soil - Termorshuizen, A. J. (American Society for Microbiology, 1998)
In a comparison of different methods for estimating Verticillium dahliae in soil, 14 soil samples were analyzed in a blinded fashion by 13 research groups in seven countries, using their preferred methods. One group analyzed only four samples. Twelve soil samples were naturally infested, and two had known numbers of microsclerotia of V. dahliae added to them. In addition, a control was included to determine whether transport had an effect on the results. Results differed considerably among the research groups. There was a 118-fold difference between the groups with the lowest and highest mean estimates. Results of the other groups were evenly distributed between these extremes. In general, methods based on plating dry soil samples gave higher numbers of V. dahliae than did plating of an aqueous soil suspension. Recovery of V. dahliae from samples with added microsclerotia varied from 0 to 59%. Most of the variability within each analysis was at the petri dish level. The results indicate the necessity to check the performance of detection assays regularly by comparing recoveries with other laboratories, using a common set of soil samples. We conclude that wet plating assays are less accurate than dry plating assays.